Laboratory pelletization of hydrochar from woody biomass - Hoekman, S. Kent; Broch, Amber; Warren, Andrew; Felix, Larry; Irvin, James (Biofuels (London), 2014)
Pelletization is an important method for increasing the mass and energy density of raw woody biomass materials and improving their handling and transport. Further increases in mass and energy density are possible by thermal pretreatment of raw biomass prior to pelletization, via torrefaction or hydrothermal carbonization (HTC). In this work, standardized laboratory test methods were developed, validated, and utilized to provide reliable assessments of pellet properties - both before and after immersion in water, as water immersion is a severe test of pellet durability. Pellets of raw or torrefied woody biomass cannot survive a standard tumbler durability test after water immersion, while pellets of hydrochar (produced by HTC processing) demonstrate excellent durability under these conditions. In part, the excellent pellet binding behavior of hydrochar is due to resins produced in the HTC process. Hydrochar can also be used as a binder to substantially improve the pelletization of raw wood and torrefied wood.